2023
DOI: 10.1111/irv.13188
|View full text |Cite
|
Sign up to set email alerts
|

Burden of respiratory syncytial virus in adults in the United Kingdom: A systematic literature review and gap analysis

Tom Wilkinson,
Steph Beaver,
Malcolm Macartney
et al.

Abstract: Despite the growing recognition of a potentially significant respiratory syncytial virus (RSV) disease burden in adults, relevant evidence in the United Kingdom (UK) is limited. This systematic literature review (SLR) aimed to identify the disease burden of RSV in UK adults, including certain high‐risk subgroups and existing evidence gaps. Published studies (2011 onwards) reporting epidemiological, economic and clinical burden outcomes in UK adults (≥15 years) with RSV were identified from indexed databases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In adults 60 years of age and older, a SR of developed countries, including Canada, found that RSV caused between 4.7% and 7.8% of symptomatic respiratory infections (7). Overall, the incidence of medically attended RSV RTI increased with increasing age (8, 9). For instance, a SR and meta-analysis (MA) found that rates of medically attended RSV RTI among adults from the United States (US) increased from 934 per 100,000 in adults 18 to 49 years of age to 1,519 per 100,000 in adults 65 years of age and older (10).…”
Section: Resultsmentioning
confidence: 99%
“…In adults 60 years of age and older, a SR of developed countries, including Canada, found that RSV caused between 4.7% and 7.8% of symptomatic respiratory infections (7). Overall, the incidence of medically attended RSV RTI increased with increasing age (8, 9). For instance, a SR and meta-analysis (MA) found that rates of medically attended RSV RTI among adults from the United States (US) increased from 934 per 100,000 in adults 18 to 49 years of age to 1,519 per 100,000 in adults 65 years of age and older (10).…”
Section: Resultsmentioning
confidence: 99%